The Quest for Aid Complementarity: Reforming Co‐operation between Nordic+ Donors and NGOs. (May 2015) - Molenaers, Nadia; Gagiano, Anna; Renard, Robrecht
<x xml:space="preserve">Abstract</x> Aid fragmentation is a maddening problem in the aid business. NGOs are part and parcel of this fragmentation problem; hence calls for more complementarity between Northern NGOs and (their) governments have led to a series of co‐funding reforms. This article analyses the co‐funding reforms of the Nordic+ donors and situates them within the broader evolutions that have taken place in donor‐NGO relations in these countries. It finds that these donors have interpreted complementarity in very different and even contradictory ways. Where some require NGOs to develop activities within the confines of the official bilateral strategy (intensive complementarity), others allow NGOs to do very different things (extensive complementarity).